Serum Metabolite Profile in Progressive Versus Nonprogressive Alcohol-Related Liver Disease: A Cross-Sectional Metabolomics Study - Puhakka, Eemeli; Ahmed, Hany; Haikonen, Retu; Leclercq, Sophie; Hanhineva, Kati; Maccioni, Luca; Amadieu, Camille; Lehtonen, Marko; Männistö, Ville; Rysä, Jaana; Stärkel, Peter; Kärkkäinen, Olli (WILEY, 2025)
Background and Aims
Alcohol-related liver disease (ALD) is a major cause of mortality and disability-adjusted life years. It is not fully understood why a small proportion of patients develop progressive forms of ALD (e.g., fibrosis and cirrhosis). Differences in the metabolic processes could be behind the individual progression of ALD. Our aim was to examine differences in serum metabolome between patients with nonprogressive ALD and patients with an early form of progressive ALD.
Methods
The study had three study groups: progressive ALD (alcohol-related steatohepatitis or early-stage fibrosis, n = 50), nonprogressive ALD (simple steatosis, n = 50) and healthy controls (n = 32). Both ALD groups took part in a voluntary alcohol rehabilitation programme. A nontargeted metabolomics analysis and targeted analysis of short-chain fatty acids were done to the serum samples taken on the day of admission.
Results
We found 111 significantly (p < 0.0005) altered identified metabolites between the study groups. Our main finding was that levels of glycine-conjugated bile acids (Cohen's d = 0.90-0.91), glutamic acid (d = 1.01), 7-methylguanine (d = 0.77) and several phosphatidylcholines (d = 0.61-0.85) were elevated in the progressive ALD group in comparison to the nonprogressive ALD group. Glycine-conjugated bile acids, glutamic acid and 7-methylguanine also positively correlated with increased levels of aspartate aminotransferase, alanine aminotransferase, gamma-glutamyl transferase, cell death biomarker M65 and liver stiffness.
Conclusions
Our results indicate that the enterohepatic cycle of glycine-conjugated bile acids, as well as lipid and energy metabolism, is altered in early forms of progressive ALD. These metabolic processes could be a target for preventing the progression of ALD.